Progress in silicon-based materials for emerging solar-powered green hydrogen (H₂) production - Aminul Islam; Md. Tarekul Islam; Teo, Siow Hwa; Hasan Mahmud; A.M. Swaraz; Ariyan Islam Rehan; Adiba Islam Rasee; Khadiza Tul Kubra; Md. Munjur Hasan; Md. Shad Salman; R.M. Waliullah; Md. Nazmul Hasan; et al. (Elsevier B.V., 2025)
The imperative demand for sustainable and renewable energy solutions has precipitated profound scientific investigations into photocatalysts designed for the processes of water splitting and hydrogen fuel generation. The abundance, low toxicity, high conductivity, and cost-effectiveness of silicon-based compounds make them attractive candidates for hydrogen production, driving ongoing research and technological advancements. Developing an effective synthesis method that is simple, economically feasible, and environmentally friendly is crucial for the widespread implementation of silicon-based heterojunctions for sustainable hydrogen production. Balancing the performance benefits with the economic and environmental considerations is a key challenge in the development of these systems. The specific performance of each catalyst type can vary depending on the synthesis method, surface modifications, catalyst loading, and reaction conditions. The confluence of high crystallinity, reduced oxygen concentration, and calcination temperature within the silicon nanoparticle has significantly contributed to its noteworthy hydrogen evolution rate. This review provides an up-to-date evaluation of Si-based photocatalysts, summarizing recent developments, guiding future research directions, and identifying areas that require further investigation. By combining theoretical insights and experimental findings, this review offers a comprehensive understanding of Si-based photocatalysts for water splitting. Through a comprehensive analysis, it aims to elucidate existing knowledge gaps and inspire future research directions towards optimized photocatalytic performance and scalability, ultimately contributing to the realization of sustainable hydrogen generation.